Auswirkungen von vereinsgebundenem Engagement auf die Drogendisposition Jugendlicher - Heigl, Josef; Eberle, Thomas; et al. (1993)

Begabung – Stärken – Talente. Evaluation eines Schulversuchs an bayerischen Mittelschulen. - Eberle, Thomas; Valentin, Katrin; Quiner, Marina (2021)

Begreifen ohne anzufassen – eine vergessene Dimension der Bildung? - Müller, Alexander; Eberle, Thomas; Gross, Sabine; Rentschler, Ingo (Bilder im Kopf. Texte zum imaginativen Lernen, 2003)

Berufsfeldbezogene Lehrerbildung unter den Bedingungen stets knapper Ressourcen - Kahlert, Joachim; Haag, Ludwig; Kiel, Ewald; Eberle, Thomas (Journal für LehrerInnenbildung, 2013)

Biografiemanagement und Kompetenzentwicklung in der Lehrerbildung - Steinherr, Eva; Weiß, Sabine; Eberle, Thomas; Braune, Agnes; Schließleder, Martina; Pollak, Guido; Kiel, Ewald (Zeitschrift für Bildungsverwaltung : ZBV, 2009)

Biographiearbeit in der Lehrerbildung – Begründung, Konzept, Methoden - Eberle, Thomas; Pollak, Guido; Schließleder, Martina (PAradigma: Beiträge aus Forschung und Lehre aus dem Zentrum für Lehrerbildung und Fachdidaktik, 2007)

Bridging the Gap: Transforming knowledge into action through gaming and simulation - Kriz, Willy C.; Eberle, Thomas (SAGSAGA, 2004)

Bridging the Gap: Transforming knowledge into action through gaming and simulation. Proceedings of the 35th Conference of the International Simulation and Gaming Association - Eberle, Thomas; Kriz, Willy Christian; Puschert, Matthias; Glötzner, Fabian (SAGSAGA, 2004)

Case Example: KIKATOPIA Game - A Simulation Game on Diversity and Living Together with Children as Co-designers. - Kriz, Willy Christian (Gaming as a Cultural Commons: Risks, Challenges, and Opportunities, 2022)
Keywords: T. Kikkawa; W.C. Kriz and J. Sugiura (Eds.)

Challenging the Challenge: Dispositions and Cognitive Processes that Promote Positive Personality Change in the Face of Risk Situations - Fengler, Janne; Eberle, Thomas; Markus, Stefan (6th European Conference on Positive Psychology, 2012)
Keywords: Sensation Seeking; Outdoor Education; Experiental Learning

Compliance and Enforcement of AI Text Generator Usage Policies in German Grammar Schools: Insights from Teenagers. - Eberle, Thomas; Adelhardt, Zinaida (International Journal of Information and Education Technology, 2025)

Concepts clarification and differentiation between smartphone addiction and compulsive internet use based on diagnostic investigation on two scales - Adelhardt, Zinaida; Markus, Stefan; Eberle, Thomas (ACM International Conference Proceeding Series, 2019)
Smartphone addiction, Internet addiction, online gaming addiction, communication addiction disorder and social network addiction are widely discussed topics nowadays. However, there is lack of distinction between different types of these technology-based addictions. The aim of this study is to investigate whether two commonly used instruments measure two different concepts as they intend to. Therefore, we made a diagnostic analysis of the Smartphone Addiction Scale (SAS-SV) for adolescents and the Compulsive Internet Use Scale (CIUS). We surveyed 96 adolescents aged between 14 and 15 years through online questionnaire. The results of the statistical analysis show that the two scales are highly correlated (r=.98, p≤.001). By using Confirmatory Factor Analysis (CFA) we stepwise reduced both instruments to their main "loading" cores to get insights in the phenomena they measure. The reduced scales stayed highly correlated. However, a combined model based on both reduced scales implies very good model fit and high reliability. We argue that both instruments measure almost the same phenomena and propose an alternative scale based on the reduction of the SAS-SV and CIUS scales - the Compulsory Mobile Internet Use Scale (CMIU). Further validation of this scale is needed. The main limitation of the study is its relatively small "convenience" sample. Further limitations and implications are discussed.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Comparison of smartphone and Internet addictions; Compulsive Internet Use Scale; Compulsory Mobile Internet Use Scale; Internet addiction; Smartphone addiction; Smartphone Addiction Scale

Der 3x2 Achievement Goal Questionnaire und das Problem der semantischen Ähnlichkeit - Jacob, Barbara; Händel, Marion; Markus, Stefan; Eberle, Thomas (79. Tagung der Arbeitsgruppe für Empirische Pädagogische Forschung der DGfE (AEPF), 2014)
Die  Debatte  um  die  Konzeptualisierung  von  Leistungszielen  ist  aus  der  Motivationsforschung  seit  zwei  Jahrzehnten  nicht mehr wegzudenken. Elliot, Murayama und Pekrun haben 2011 mit dem 3x2–Modell der Achievement Goals eine Erweiterung der  bisherigen  Modelle vorgestellt,  die  der  dichotomen  Wertkomponente  (Annäherung  vs.  Vermeidung)  einen evaluativen Standard zur Definition von Kompetenz (selbstbezogen, aufgabenbezogen, fremdbezogen) hinzufügt. Die postulierte Struktur der  Leistungsziele  haben  die  Autoren  mit Hilfe des  Achievement  Goal  Questionnaire  (AGQ)  bestätigt.  Beim  Einsatz  des  AGQ zeigen  sich  jedoch  starke  Interkorrelationen  zwischen  den  einzelnen  Komponenten  sowie  den  Evaluationsstandards (vgl. Johnson & Kestler, 2013). Sehr hohe Korrelationen traten auch in früheren eigenen Studien der Autoren auf, daher stellt sich die  Frage,  inwieweit  tatsächlich  unterschiedliche  Zielsetzungen erfasst  werden.  Diesem  Problem  könnte  ein  potentieller Response Bias durch die semantische Ähnlichkeit der Items zugrunde liegen (vgl. Murayama et al., 2011). Erstes  Ziel  der  vorliegenden  Studie  ist  es,  die  3x2-faktorielle  Struktur  des  AGQ  in  einer  deutschen  Fassung  zu  replizieren. Zweitens soll überprüft werden, ob sich ein Response Bias durch eine zeitliche Trennung der Erfassung ähnlicher Items reduzieren lässt. Für die Studie wurden die Daten von N = 314 Lehramtsstudierenden in einer Psychologievorlesung zu zwei Zeitpunkten (t1 = zwei Wochen vor der Abschlussklausur, t2 = eine Woche vor der Abschlussklausur) erhoben. Die Studierenden wurden dabei randomisiert in drei  Gruppen eingeteilt. Von ihnen  erhielt  Gruppe A zu t1 zuerst die  Annäherungsziele, Gruppe B zuerst die Vermeidungsziele und dann zu t2 die jeweils andere Wertkomponente zur Bearbeitung.  Gruppe C beantwortete ausschließlich zu t2 alle Items auf einmal. Die Reliabilitäten der Einzelskalen waren insgesamt gut (self-approach α = .89, self-avoidance α = .80, task-approach α = .65, task-avoidance α = .69, other-approach α =.90, other-avoidance α = .87). Die Faktorstruktur des 3x2-Modells konnte in einer CFA bestätigt werden (χ² = 18.457, df = 6, CFI = .98, RMSEA = .08; SRMR = .01). Die Interkorrelationen der Zielorientierungen bei Gruppe C (alle Ziele gleichzeitig bearbeitet) fielen erwartungskonform relativ hoch aus (.40 < r < .83). Für die Gruppen A und B, die die Items zu Annäherungs- und Vermeidungszielen zu verschiedenen Zeitpunkten  beantworteten,  zeigten  sich  insgesamt  niedrigere  Korrelationen  (.30  < r <  .79),  die  Korrelationsunterschiede waren signifikant (p < .05). Die semantische Ähnlichkeit der Items ruft folglich einen Response Bias hervor. Dieser ist durch eine zeitlich versetzte Beantwortung  der  ähnlichen  Items  verminderbar.  Ob  sich  eine  zeitversetzte  Variante  jedoch  bei  zukünftigen  Erhebungen  realisieren lässt, soll diskutiert werden.
Keywords: Motivation; Achievement Goals; Response Bias

Der inklusive Blick über den schulischen Tellerrand – Was Bildungseinrichtungen von außerschulischen Inklusionsprojekten lernen können - Markus, Stefan; Eberle, Thomas (Pädagogik, 2015)
Keywords: Inklusion; Erlebnispädagogik; Rollstuhlsport; Non-formale Bildungsorte; informelles Lernen

Die Auswertungsphase von Planspielen - Eberle, Thomas (Tutzinger Didaktikforum Planspiele in der politischen Bildung, Politische Akademie Tutzing in Kooperation mit der Bundeszentrale für politische Bildung, 2011)

Die Bedeutung von Emotionen im erlebnispädagogischen Lernkontext - Markus, Stefan; Eberle, Thomas; Jacob, Barbara (Handbuch Erlebnispädagogik, 2018)

Differenzierung 2.0 - Eberle, Thomas; Kuch, Helge; Track, Sabine (Heterogene Klassen - Differenzierung in Schule und Unterricht (3. Auflage), 2014)

Differenzierung 2.0 - Eberle, Thomas; Kuch, Helge; Track, Sabine (Heterogene Klassen – Differenzierung in Schule und Unterricht, 2011)

Effects of a long-term separation from online gaming on teenagers' gaming habits - Adelhardt, Zinaida; Eberle, Thomas (Proceedings of the 6th European Conference on Social Media, ECSM 2019, 2019)
Teenagers' preoccupation with online video games is a widely discussed topic. The vast majority of research deals with negative effects of "gaming": violence, depression, and diminishing academic performance. Internet gaming disorder (IGD), video game addiction (VGA) or pathological video gaming (PVG)-an addictive tendency towards video gaming affects millions of gamers across the globe. The prevention of potential addictive behaviour and intervention in case of excessive usage is a complicated issue. Our aim was to evaluate adolescents' reaction to the separation from the world of media and its long-term influence on teenagers' video game usage. Each year, 34 fourteen-and fifteen-year-old adolescents sail around the globe for half a year and thus have the opportunity to challenge their abilities in the real world. Smartphone usage and computer gaming are not allowed while sailing, although adolescents may use their devices during some land-stops. We gathered data before the trip (October 2017), after being separated from computers and smartphones for three weeks (November 2017), at the end of the trip (April 2018) and five months after it (September 2018). Research instruments included standardised questionnaires and in-depth interviews. Teenagers, especially boys, were found to play mostly social games and communicate through these games with those whom they already know offline. Results show that during the trip the teenagers' attitudes towards media have significantly changed and this change remained constant five months after the intervention. Video gaming has dropped significantly (d=.0.362). Video gaming was also found to be correlated with positive attitudes towards media and technology and with such media usage patterns as Internet searching and media sharing. While most of the teenagers completely quitted online gaming after the trip, habits of one teenager-who has demonstrated especially addictive behaviour before the trip-stayed unchanged after our intervention: he continued playing online games several hours a day. Implications, further research perspectives and limitations will be presented and discussed.
CRIS-Team Scopus Importer:2019-08-09
Keywords: Attitudes towards media; Excessive gaming; Online video gaming; Social gaming; Teenagers' media usage

Effects of experiencing outdoor challenges – canyoning - Eberle, Thomas (Bridging the Gap: Transforming knowledge into action through gaming and simulation. Proceedings of the 35th Conference of the International Simulation and Gaming Association, 2004)

Effects of experiencing outdoor challenges – canyoning - Eberle, Thomas (Bridging the Gap: Transforming knowledge into action through gaming and simulation, 2004)

Efficacy in German Teacher Education - Kiel, Ewald; Weiß, Sabine; Eberle, Thomas (Canadian social science, 2012)

Ein Beitrag zur Medienerziehung in der Hauptschule. Schüler der 7. Jahrgangsstufe stellen ihre Schule im Videofilm dar - Vorbereitung, Durchführung und Reflexion des Vorhabens - Eberle, Thomas (1991)

Einflussfaktoren auf die Entwicklung allgemeiner und spezifischer Selbstwirksamkeitserwartungen in mehrtägigen erlebnispädagogischen Interventionen - Markus, Stefan; Eberle, Thomas; Fengler, Janne (Empirische Pädagogik, 2019)

Einflussfaktoren auf die Entwicklung allgemeiner und spezifischer Selbstwirksamkeitserwartungen in mehrtägigen erlebnispädagogischen Interventionen. Erlebnispädagogik. - Eberle, Thomas; Markus, Stefan; Fengler, Janne (2019)

Einsatz von Planspielen in Unternehmen - Eberle, Thomas; Kriz, Willy Christian (Personal-Manager, 2012)

Einsatz von Planspiel in der Organisationsentwicklung an Hochschulen - Eberle, Thomas (Planspiele für die Organisationsentwicklung, 2007)

Embodiment in der Pädagogik. - Eberle, Thomas; Awad, Sarah; Ziegler, Alexander (Empirische Pädagogik, 2021)

Emotionale Varianz bei Schülern in leistungsorientierten erlebnispädagogischen Interventionen - Jacob, Barbara; Markus, Stefan; Roth, Sibylle; Eberle, Thomas (Jahrestagung für Empirische Unterrichtsforschung, 2013)
Keywords: Emotion; Erlebnispädagogik

Emotional Experiences of Students in Achievement Tasks in an Outdoor Educational Setting - Jacob, Barbara; Markus, Stefan; Roth, Sibylle; Eberle, Thomas (15th Biennial EARLI Conference, 2013)
The last decade brought new insights into emotions linked to achievement settings. They are related to students´ motivation, learning and performance, typically being experienced before, during, and after achievement situations. Emotions refer to the activity itself or the related outcome. Achievement goals are competence-relevant aims for individuals and crucial for achievement motivation. Researchers distinguish them into mastery and performance goals. The first indicates the development of competence, the latter its demonstration. A further bifurcation into approach and avoidance tendencies of these two types of goals has been established. So far quantitative research on these topics in outdoor education has been lacking.   Our study prospectively investigates the emotional experiences of school and outdoor educational interventions and the interactions with achievement goal orientations.   34 high school students (10th grade) started in October 2012 on a six-month sailing tour across the Atlantic Ocean. They will answer three different versions of a questionnaire (before, during, after achievement) measuring state emotions (enjoyment, pride, shame, hope, hopelessness, anger, anxiety, and boredom) in different achievement settings: school pedagogical situations like “ordinary” lessons and tests, as well as outdoor educational tasks (like navigating the ship, autonomously organizing of field trips in Cuba or Panama, leading the group, climbing the rigging and mountains). Furthermore, approach and avoidance goal orientations (the latter as states and traits) will be assessed. In all, 39 measurements per participant will be taken. First results will be presented at the conference.
Keywords: Emotion; Goal orientation; Experiental Learning

Empirische Annäherung an die Wirksamkeit von Outdoor-Trainings und die Bedeutung von Reflexionsphasen – Erste Ergebnisse einer Vergleichsstudie - Eberle, Thomas (Perspektiven zur Weiterentwicklung der Erlebnispädagogik. Schwerpunkte Ethik und Evaluierung. Hochschulforum Erlebnispädagogik Augsburg 2000 und 2001, 2002)

Entwicklungsförderung Adoleszenter durch eine erlebnispädagogische Langzeitintervention am Beispiel „Klassenzimmer unter Segeln“ - Jacob, Barbara; Markus, Stefan; Adelhardt, Zinaida; Eberle, Thomas (Empirische Pädagogik, 2019)

Entwicklung und Einsatz standardisierter Erhebungsinstrumente in Praxisprojekten – Messung von Effekten auf Selbstkonzept, Sozialverhalten und Arbeitsatmosphäre - Eberle, Thomas (Lernkultur und Kulturelle Bildung, 2008)

Erfahrungsorientiertes Lernen mit Planspiel, Erlebnispädagogik und Outdoor-Training - Eberle, Thomas (Handbuch: Planspiele in der politischen Bildung, 2017)

Erleben von Schülern während und nach dem Klettern, Sichern und Abseilen - Eberle, Thomas (Erleben und lernen, 2010)

Erlebnispädagogik. - Eberle, Thomas; Fengler, Janne (Empirische Pädagogik, 2019)

Erlebnispädagogik - Eberle, Thomas; Fengler, Janne (Empirische Pädagogik, 2019)

Evaluation von Outdoor-Trainings - Eberle, Thomas (Praxishandbuch Bildungscontrolling für exzellente Personalarbeit. Konzepte – Methoden – Instrumente –Unternehmenspraxis, 2005)

Experiential Learning Outdoors – Participant’s feedback on different activities - Eberle, Thomas (Bridging the Gap: Transforming knowledge into action through gaming and simulation. Proceedings of the 35th Conference of the International Simulation and Gaming Association, 2004)

Experiential Learning und Embodied Cognition in erlebnispädagogischen Lernsettings. - Eberle, Thomas; Ziegler, Alexander (Empirische Pädagogik, 2021)

Exploring the Relationship between Social Networking Addiction, Fear of Missing Out, Loneliness and TikTok Use among Adolescents. - Eberle, Thomas; Adelhardt, Zinaida (Journal of Addiction & Addictive Disorders, 2024)

Extending the UTAUT Framework: Adoption and Usage Patterns of AI Text Generators among teenagers in German grammar schools. - Eberle, Thomas; Adelhardt, Zinaida (6th International Conference on Education Development and Studies, 2025)

Fallbasiertes Arbeiten in der Lehrerbildung - Hopperdietzel, Hartmut; Eberle, Thomas; Kiel, Ewald; Haag, Ludwig; Kahlert, Joachim; Steinherr, Eva (Journal für Lehrerinnen- und Lehrerbildung, 2008)

Fallbasiertes Lernen in der Lehrerbildung - Eberle, Thomas (76. Tagung der Arbeitsgruppe für Empirische Pädagogische Forschung der DGfE (AEPF), 2011)

Fallbasiertes Lernen in der Lehrerbildung. Möglichkeiten der Integration von Theorie und Praxis - Eberle, Thomas; Haag, Ludwig; Kahlert, Joachim; Kiel, Ewald (Professionalität erweitern, Lehrer bilden, Schüler fördern, 2007)

Fernsehen, ein bedeutsamer gesellschaftlicher Faktor – Spielräume medienpädagogischen Handelns - Eberle, Thomas (1988)

Fernsehverhalten Jugendlicher. Nutzung und motivationale Aspekte unter besonderer Berücksichtigung des Reality-TV - Eberle, Thomas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1999)

Förderung des Selbstkonzepts durch erlebnispädagogische Lernsettings - Eberle, Thomas; Fengler, Janne (Handbuch Erlebnispädagogik, 2018)

Förderung von Selbstwirksamkeitserwartungen durch Erlebnispädagogik - Markus, Stefan; Eberle, Thomas; Fengler, Janne (Handbuch Erlebnispädagogik, 2018)

Forschungsbericht 1, Ergebnisse der Zwischenevaluation über das Exercitium Paedagogicum, Evaluation eines Modellversuchs zur Reform schulischer Praktika - Eberle, Thomas; Kopp, Bärbel; Martschinke, Sabine (2006)

Forschung und Anlage wissenschaftlicher Studien in den Bereichen experiential learning, Planspiel und Simulation - Eberle, Thomas (SAGSAGA-Tagung, 2012)

Gesellschaft – Schule – Kind. Grundfragen der Erziehung - Heigl, Josef; Zöpfl, Helmut; Eberle, Thomas (Bauer, 1997)

Gesundheit als lebenslanges Lernen - Eberle, Thomas (Europäisches Gesundheitsforum 2009, 2009)

Gleiche Aktivitäten für unterschiedliche Teilnehmer? Stand der Forschung über erlebnispädagogische Schullandheimaufenthalte. Konsequenzen für die Praxis - Forschungsdesiderate - Eberle, Thomas (Jahrestagung des wissenschaftlichen Beirats der Gesellschaft für Erlebnispädagogik GfE, 2013)

Grenzerfahrung in den Experiential Learning-Lernsettings Erlebnispädagogik, Planspiel und Outdoor-Training - Eberle, Thomas (Beyond erziehungswissenschaftlicher Grenzen. Diskurse zur Entgrenzung der Disziplin, 2019)

Heimliche Lehrpläne in der Lehrerbildung – Auswirkungen struktureller Defizite sowie unterschiedlicher Vorstellungen und Ziele auf die Professionalisierung von Lehrkräften - Eberle, Thomas (Lernen und Entwicklung im globalen Kontext. „Heimliche Lehrpläne“ und Basiskompetenzen, 2008)

Herausfordernde Situationen in der Schule : ein fallbasiertes Arbeitsbuch - Kiel, Ewald; Kahlert, Joachim; Haag, Ludwig; Eberle, Thomas (Klinkhardt, 2011)

How intelligent, popular and nice are high achieving students according to the perceptions of their school teachers? Results of a cross-cultural study with teachers from eight countries - Leana-Tasçilar, MarilenaZ.; Blumen, S; Eberle, Thomas; Escobedo, P. S.; Jurisevic, M; Li, X.; Roy, P.; Sak, U.; Shi, J; Vialle, W; Ziegler, Albert (Talents in Motion, 2016)

„Ich schaff das!“ Wie die Bewältigung von Herausforderungen die Selbstwirksamkeit steigern kann: Ein empirischer Beitrag zur Wirkungsforschung in der Erlebnispädagogik - Markus, Stefan; Fengler, Janne; Eberle, Thomas (Erleben und lernen, 2016)

Individuelle Stärken-Schwächen-Analyse und Kompetenzentwicklung in der Lehrerbildung - Steinherr, Eva; Weiß, Sabine; Braune, Agnes; Eberle, Thomas; Kiel, Ewald (Zeitschrift für Bildungsverwaltung : ZBV, 2011)

Influence of long-term experiential learning and sailing adventure on teenage personality development - Eberle, Thomas; Adelhardt, Zinaida; Jacob, Barbara; Markus, Stefan (Proceedings of the 9th SELF Biennial International Conference (SELF2017), 2017)

Innovativer Englischunterricht mit selbst gestalteten Hörfunkelementen - Eberle, Thomas (Tagung „Differenzierung im Englischunterricht“, 2010)

Innovativer Englischunterricht mit selbst gestalteten Hörfunkelementen - Eberle, Thomas (Differenzierung im Englischunterricht : Dokumentation zur Tagung am 12./13. März 2010 an der Friedrich-Alexander-Universität Erlangen-Nürnberg, 2010)

Innovativer Englischunterricht mit selbst gestalteten Hörfunkelementen - Eberle, Thomas (Differenzierung im Englischunterricht, 2011)

Jeder hat Talent - Valentin, Katrin; Eberle, Thomas; Mahling, Marina (Pädagogik, 2019)

Klassenzimmer unter Segeln - Eberle, Thomas (Erleben und lernen, 2019)

Klassenzimmer unter Segeln - Eberle, Thomas; Markus, Stefan; Adelhardt, Zinaida (Jahrbuch Schulleitung 2020 (1. Auflage), 2020)

Klassenzimmer unter Segeln (Themenheft Neue Medien und Medium Wasser – alles im Fluss). - Eberle, Thomas (Erleben und lernen, 2019)

Kommentar zum Fachlehrplan Mathematik 5/6 – Gegenstandsbereich Zahlen und Operationen. - Eberle, Thomas; Schön, Konstanze; Reichel, Felix (Lehren und Lernen in der bayerischen Mittelschule 5/6. Kommentare und Unterrichtshilfen zum LehrplanPLUS Mittelschule. Jahrgangsstufen 5 und 6, 2017)

Kopf, Herz und Hand: Ein empirischer Blick auf zentrale Dimensionen erlebnispädagogischer Lernprozesse - Eberle, Thomas; Fengler, Janne; Markus, Stefan (11. Internationaler Kongress erleben und lernen, 2016)

Kopf, Herz und Hand: Ein empirischer Blick auf zentrale Dimensionen erlebnispädagogischer Lernprozesse - Markus, Stefan; Eberle, Thomas; Fengler, Janne (Erfolgreiche Erlebnispädagogik gestalten! Nachspüren – Querdenken – Mitmachen, 2016)

Learning from Challanging Situations - Eberle, Thomas (Konferenz der International Simulation and Gaming Association (ISAGA), 2011)

Lehrer werden ist nicht schwer…?! Die problematische Studienwahl von Lehramtsstudierenden - Kiel, Ewald; Pollak, Guido; Eberle, Thomas; Braune, Agnes; Schließleder, Martina (Pädagogik, 2007)

Lernen im Outdoor-Training. Effekte auf Selbstkonzept und Teamkompetenz im hochschuldidaktischen Kontext - Eberle, Thomas (2008)

Little Einstein in my classroom: results of a cross-cultural study with teachers - Jurisevic, M; Blumen, S; Eberle, Thomas; Sánchez-Escobedo, P; Park, K; Roy, P; Sak, U; Li, X; Shi, S; Leana-Tasçilar, MarilenaZ.; Vialle, W; Ziegler, Albert (Educational change: Challenges and expectations, 2016)

Maßnahmen zur Förderung des Ehrenamtes im Bayerischen Fußballverband. Ergebnisse der empirischen Studie - Eberle, Thomas (1995)

Medienbildung in der Schule - Eberle, Thomas (Medienbildung in schulischen Kontexten : erziehungswissenschaftliche und fachdidaktische Perspektiven, 2013)

Medienerzieherische und mediendidaktische Konzepte - Eberle, Thomas (Studienbuch Schulpädagogik, 2013)

Mit Sprechen durchstarten. Förderung von Sprach-, Sozial- und Selbstkompetenz mittels Hörfunkprojekten. Theorie, Didaktik, praktische Beispiele - Eberle, Thomas (2010)

Motivation des Fernsehverhaltens Jugendlicher. Grundlagen, Verhaltensanalyse, Selbstauskünfte und Beurteilung des Reality-TV - Eberle, Thomas (Klinkhardt, 2000)

Naturbegegnung und Gesundheitsförderung. - Eberle, Thomas; Fengler, Janne (Empirische Pädagogik, 2022)

Naturbegegnung und Gesundheitsförderung. Impulse für Theorie, Empirie und Praxis der Gesundheits- und Erlebnispädagogik. - Eberle, Thomas; Fengler, Janne (Empirische Pädagogik, 2022)

Neue Medien und Kreativitätsförderung in der Grundschule - Eberle, Thomas (Kreativität und Grundschule, 2000)

Niedrige Seilaufbauten - Grundlagen über verwendetes Material , Aufbau- und Anschlagmethoden - Boneberger, Hannes; Eberle, Thomas (Erleben und lernen, 2009)

Outdoor-Lernsettings – Was bringen sie für Indoor? - Eberle, Thomas (Adventure, Erlebnis und Bildung. Adventuremanagement in Theorie und Praxis, 2016)

Outdoor-Training in der Lehrerfortbildung - Einsatz und Effekte im Rahmen schulischer Organisationsentwicklung - Eberle, Thomas (Lehrerinnen und Lehrer lernen : Konzepte und Befunde zur Lehrerfortbildung, 2010)

Personalentwicklung mit Planspiel und Outdoor-Training – Theoretische Grundlagen, Gemeinsamkeiten und Unterschiede - Eberle, Thomas (Planspiele in der beruflichen Bildung - Multimedia-Publikation (Fachbuch mit CD-ROM) (3. Aufl.), 2003)

Personalentwicklung mit Planspiel und Outdoor-Training – Theoretische Grundlagen, Gemeinsamkeiten und Unterschiede - Eberle, Thomas (Planspiele in der beruflichen Bildung (4. Aufl.), 2005)

Personalentwicklung mit Planspiel und Outdoor-Training – Theoretische Grundlagen, Gemeinsamkeiten und Unterschiede - Eberle, Thomas (Planspiele in der beruflichen Bildung (4. erweiterte Auflage; Multimedia-Publikation mit CD), 2008)

Personnel development through gaming simulation and outdoor training: Fundamental principles, similarities and differences, empirical studies - Eberle, Thomas (Social contributions and responsibilities of simulation and gaming. Proceedings of the 34th annual conference of the International Simulation and Gaming Association (ISAGA), 2003)

Planspiele in der Hochschullehre und Hochschuldidaktik - Eberle, Thomas; Kriz, Willy C. (Handbuch: Planspiele in der politischen Bildung, 2017)

Planspieleinsatz an Schulen jenseits des Üblichen - Eberle, Thomas (Tutzinger Didaktikforum Planspiele in der politischen Bildung, Politische Akademie Tutzing in Kooperation mit der Bundeszentrale für politische Bildung, 2011)

Planspiele und Simulation als Instrument der Entwicklung und Beratung - Eberle, Thomas (Tagung der EOS (Organisation für Organisations- und Schulentwicklung), 2013)

Planspiel und Simulationen als Lernumgebung – Grundlagen - Eberle, Thomas (Tutzinger Didaktikforum Planspiele in der politischen Bildung. Politische Akademie Tutzing in Kooperation mit der Bundeszentrale für politische Bildung, 2013)

Professionalisierungstheorie als Grundlage von Lehrerbildung und Lehrerbildungsforschung - Eberle, Thomas; Pollak, Guido (Vierteljahrsschrift für wissenschaftliche Pädagogik, 2006)

Promoting general and specific self-efficacy beliefs by experiential education programs in the outdoors - Markus, Stefan; Eberle, Thomas; Fengler, Janne (8th SELF Biennial International Conference, 2015)
Transfer effects of experiential education programs depend on the participants' perceived level of challenges (Eberle, 2008). Different types of challenges, peak and limit experiences (Fengler, 2010) may influence sub-dimensions of self-efficacy beliefs (Schmitz, 2002). The aim of our study is to evaluate the structure of general and specific self-efficacy beliefs, their antecedents and development in an outdoor-educational setting. Positive effects are assumed on all self-efficacy sub-dimensions depending on the particular perceived level of challenge and the appraisal of success. Furthermore, we investigate the emotional experiences of participants during the intervention as well as interaction effects with achievement motives, risk and competition seeking, domain-specific values and self-efficacy beliefs. In our study, N=544 students from German secondary schools (8th to 11th grade) were asked by questionnaire before and after a one-week outdoor-educational intervention about certain beliefs (traits). Additionally, we measured their emotions and on-task-beliefs (states) after three randomly selected adventure educational tasks. Research is in progress. First findings show acceptable to good reliabilities of the scales. General, emotional and cognitive self-efficacy beliefs show significant increases. Positive emotions correlate positively with self-efficacy increase on a significant low to medium level. Implications for experiential education programs as well as school education will be discussed.
Keywords: Outdoor Education; Erlebnispädagogik; Selbstwirksamkeit; Self-efficacy

Rezension zu: Bernd Heckmair, Werner Michl: Von der Hand zum Hirn und zurück - Eberle, Thomas (2013)

Rezension zu: Konstanze Thomas, Astrid Habiba Kreszmeier (Hrsg.): Systemische Erlebnispädagogik - Eberle, Thomas (2008)

Rezension zu: Tanja Kinne, Georg Theunissen (Hrsg.): Erlebnispädagogik in der Behindertenarbeit - Eberle, Thomas (2014)

Rezension zu: Werner Michl: Erlebnispädagogik - Eberle, Thomas (2010)

Seilaufbauten als erlebnispädagogisches Lern-Setting - Eberle, Thomas; Boneberger, Hannes (Erleben und lernen, 2009)

Sensation Seeking. Risiko- und/oder Schutzfaktor? - Eberle, Thomas; Fengler, Janne (Jahrestagung der Deutschen Gesellschaft für Medizinische Psychologie und Psychopathometrie DGMPP, 2012)

Six Months of "Digital Death": Teenagers' Reaction on Separation from Social Media - Adelhardt, Zinaida; Markus, Stefan; Eberle, Thomas (5th European Conference on Social Media, 2018)

Six Months of "Digital Death": Teenagers' Reaction on Separation from Social Media - Adelhardt, Zinaida; Markus, Stefan; Eberle, Thomas (Proceedings of the 5th European Conference on Social Media (ECSM 2018), 2018)
CRIS-Team WoS Importer:2019-04-04

Social Media Withdrawal: What Social Media Services and Activities Teenagers miss when they are “switched-off”? - Adelhardt, Zinaida; Eberle, Thomas (Proceedings of the 10th European Conference on Social Media, ECSM 2023, 2023)
Nowadays teenagers grow up with social media and various possibilities of digital communication. The offline and online lives of “digital natives” are tightly bound together and for most of them life without Internet is unthinkabe. However, what happens when teenagers do not have access to modern communication facilities and to social media? Do they miss these media? What services and which activities do teenagers miss? We gathered qualitative data from teenagers after three weeks of being completely offline in frames of a long-term adventure education program. We also gathered quantitative data on teenage media use before media withdrawal. 135 teenagers (M=14.47, SD = .56, 52% female) answered our questions within four years (34 teenagers in each of these years - 2018, 2019, 2020 - and 33 teenagers in 2021). After three weeks of complete media withdrawal two thirds of teenagers reported not missing social media or missing them to a minor extent. They described social media services as stressful, disturbing, extremely time-consuming and boredom-related. Several respondents replied that they had enough communication offline and felt good in the community that made online social media superfluous. However, every third teenager reported missing social media. The main reason was the desire to contact the personal social network. A few teenagers reported missing social media as a source of relaxation and an efficient way to “switch-off”. One out of four teenagers (23%) reported missing WhatsApp. One out of ten (11%) mentioned Instagram, but just one half in a context of missing it. WhatsApp and Instagram were also the most popular services among teenagers before withdrawal (94.3% of teenagers reported having a profile in WhatsApp and 73,3% of teenagers reported using Instagram). Only a few teenagers (2.2%) - all boys - mentioned missing YouTube. The article presents further results, discusses perspectives and limitations of the project.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Boredom; Gender Differences In Social Media Use; Instagram; Media Withdrawal; Media-Related Stress; Social Media Use Among Teenagers; Whatsapp; Youtube

Studien- und Berufswahlmotivation von Lehramtsstudierenden - Eberle, Thomas; Pollak, Guido (PAradigma: Beiträge aus Forschung und Lehre aus dem Zentrum für Lehrerbildung und Fachdidaktik, 2006)

Studium Grundschullehramt: Zur problematischen Kompatibilität von Studien-/Berufswahlmotiven und Berufsvorstellungen - Weiß, Sabine; Braune, Agnes; Pollak, Guido; Eberle, Thomas; Kiel, Ewald (Zeitschrift für Grundschulforschung, 2009)

Subdimensions of Students’ Perceived Autonomy Support and Their Relationship to Achievement Emotions - Markus, Stefan; Jacob, Barbara; Eberle, Thomas (21st JURE (Junior Researchers of EARLI) Conference, 2017)

Talentförderung an der Mittelschule. Impulse für Unterricht und Schulentwicklung. - Valentin, Katrin; Eberle, Thomas; Mahling, Marina (SchulVerwaltung Bayern, 2018)

Teenagers’ Reaction on the Long-Lasting Separation from Smartphones, Anxiety and Fear of Missing Out - Adelhardt, Zinaida; Markus, Stefan; Eberle, Thomas (SMSociety '18: Proceedings of the 9th International Conference on Social Media and Society, 2018)

The 4I Model of Benefits and its Integration with the Technology Acceptance Model (TAM): Teenagers’ Perspectives on Using ChatGPT for Homework - Adelhardt, Zinaida; Eberle, Thomas (Proceedings of the 4th International Conference on AI Research, ICAIR 2024, 2024)
The introduction of ChatGPT has provided students with a tool similar to a fairy-tale djinn, giving the ability to simplify homework and projects with just a few keystrokes. This study examines teenagers' perspectives on using ChatGPT for homework, exploring both the perceived benefits and concerns. Based on content analysis of responses from 141 teenagers aged 14 to 16 from grammar schools across various federal regions in Germany, we introduce the 4I Model of Benefits, identifying four key advantages: Information, Inspiration, Improvement, and Immediacy. Integrated within the Technology Acceptance Model (TAM) framework, this model clarifies factors influencing teenagers’ acceptance of AI text generators in education. Findings indicate that, while most teenagers recognize the distinct benefits of using ChatGPT, concerns about learning efficacy and over-reliance underscore the need for balanced educational integration. By enriching the TAM framework, the 4I Model identifies the specific benefits of ChatGPT that drive its acceptance and provides valuable insights for educators, policymakers, and developers.
CRIS-Team Scopus Importer:2025-02-04
Keywords: 4I model of AI benefits; ChatGPT in education; Educational benefits of AI text generators; Homework support through AI; Technology acceptance model (TAM) Extension; User studies

The Assessment of Sensation Seeking and Correlations with other Personality Factors - Fengler, Janne; Eberle, Thomas; Markus, Stefan (30th International Congress of Psychology, 2012)
Keywords: Sensation Seeking; Outdoor Education

Trainingsgestaltung auf der Basis empirischer Ergebnisse - Eberle, Thomas (Menschen stärken für globale Verantwortung, 2008)

Unterrichtsanalyse und pädagogisches Handeln. Theoretische Grundlegungen und praktische Anregungen zur lernwirksamen Gestaltung des schulpädagogischen Blockpraktikums - Serve, Helmut J.; Eberle, Thomas (PimS., 1998)

Unterwegs auf bewegenden Wegen – theoretisch, praktisch, empirisch - Eberle, Thomas (Kongress „erleben und lernen“, 2010)

Unterwegs auf bewegenden Wegen - theoretisch, praktisch, empirisch - Eberle, Thomas (Erleben und lernen, 2010)

Utilizar los juegos para aprender a resolver conflictos - López Ros, Victór; Eberle, Thomas (TÁNDEM. Didáctica de la educación física, 2003)

Veränderungen von Selbstkonzept, Sozialverhalten und Arbeitsatmosphäre von Schülerinnen und Schülern im "Praxisforschungsprojekt - Leben Lernen". Ergebnisse der quantitativen Fragebogenerhebung und der inhaltsanalytischen Auswertung - Eberle, Thomas ("Ich hab gar nicht gemerkt, dass ich was lern" Untersuchungen zu künstlerisch-kulturpädagogischer Lernkultur in Kooperationsprojekten mit Schulen, 2009)

Veränderung von Selbstkonzept, Sozialverhalten und Arbeitsatmosphäre im gebundenen Ganztag (Forschungsbericht mit Längs- und Querschnittsdaten) - Eberle, Thomas (Tagung Kulturelle Bildung im gebundenen Ganztag, 2011)

Voraussetzungen und Möglichkeiten aktiver Medienpädagogik - Eberle, Thomas (1989)

Wahl des Studienortes Passau - Eberle, Thomas; Pollak, Guido (PAradigma: Beiträge aus Forschung und Lehre aus dem Zentrum für Lehrerbildung und Fachdidaktik, 2007)

Welche Bildung braucht Schule heute? Erlebnis- und Erfahrungsorientierung als Desiderata zukunftsfähiger Schulpädagogik - Eberle, Thomas (Tagung der ReligionspädagogInnen an bayerischen Universitäten (KRBU), 2011)

What Impact do Experiential Education Programs in the Outdoors have on Participants’ Self-Efficacy Beliefs? - Fengler, Janne; Markus, Stefan; Eberle, Thomas (2nd World Conference on Personality, 2016)

Wirksamkeit von Lehrerbildung - Biografiemanagement und Kompetenzentwicklung in der dreiphasigen Lehrerbildung - Kiel, Ewald; Pollak, Guido; Weiß, Sabine; Braune, Agnes; Steinherr, Eva; Schließleder, Martina; Habereder, Helmut; Eberle, Thomas (LMU, Lehrstuhl für Schulpädagagogik, 2011)

YouTube as a Source of Educational Content in Teenagers' Learning Practices - Adelhardt, Zinaida; Eberle, Thomas (Proceedings of the 9th European Conference on Social Media, 2022)
YouTube is one of the most popular online social spaces nowadays combining features of both a huge repository of information and a social networking service. Millions of people use this video-sharing platform daily. Entertainment (sports, comedy, music, movie trailers), information seeking (missed news, product reviews, research on a specific topic), and educational purposes (how-to videos, learning math, or tactics for video games) were discussed as main motivational aspects for watching YouTube videos (Lagger et al. 2017). Usage of YouTube for educational purposes became particularly relevant for teenagers as a support for their home-schooling. Our goal is to find out what strategies teenagers use to find relevant educational content on the service and how important this content was for their everyday learning practices before and during the COVID pandemic. We analyzed online behavior of 34, 14 to 15-year old teenagers (47% male) who took part in a long-term adventure trip with digital media left aside. We gathered quantitative data seven months before the trip (March 2019), just before the trip (October 2019), on the last day of the trip (April 2020), and five months after the trip (September 2020). We also conducted in-depth interviews with nine teenagers, who named YouTube as their favourite online service. Our intention is now to conduct nine additional interviews with the same teenagers to see whether their everyday learning practices changed within the last year. Implications drawn from this study, further research perspectives, and limitations will be presented and discussed.
CRIS-Team Scopus Importer:2024-12-16
Keywords: educational benefits of YouTube; online learning; social media overuse; teenage usage of social networks; YouTube usage patterns